Second primary cancers after cancer of unknown primary in Sweden and Germany: efficacy of the modern work-up - Liu, Hao; Hemminki, Kari; Brenner, Hermann (European journal of cancer prevention, 2013)
the rates of specific SPCs found after the work-up of CUP and the more sign/symptom-directed diagnostic approaches applied after any other cancer. The number of CUP patients identified in the nationwide Swedish database and nine German cancer registries was 24 641 from 1997 through 2006, and rate ratios (RRs) for SPCs were recorded in two follow-up periods. The detection rate of SPCs immediately after any other cancer was about two times higher in Germany than in Sweden, but the rate immediately after CUP was almost the same for the two datasets. In the joint analyses after CUP, the RRs of liver, lung, breast, and kidney cancers were higher than after any other cancer, whereas the RRs of prostate, urinary bladder, and connective tissue cancers as well as non-Hodgkin’s lymphoma were not significantly different; the RR of cancers of upper aerodigestive tract was lower after CUP than after any other cancer. The joint data indicate that the work-up is efficient in detecting tumors in the thoracoabdominal organs that are screened by computed tomography. For some other organ sites, the more sign/symptom-directed diagnostic approaches may be equally efficient. However, none of the applied techniques could detect all tumors immediately after the first diagnosis....